ACUTE BUFFALO MASTITIS CAUSE BY MIXED INFECTION OF Enterobacter cloacae AND Proteus mirabilis AT BASRAH, IRAQ - Mohanad H. Lafta (Basrah Journal of Veterinary Research)
Mastitis caused by Proteus mirabilis and Enterobacter cloacae has been investigatedand diagnosed. Milk samples carried-out from fifteen local buffalo breeds reared in Basrah, Iraq.Ten clinically healthy local buffalo breeds were considered and controls. Diseased buffalo showsigns of pain, swelling, redness of the udder, watery consistency with the light red color of themilk, with high systemic reactions including significant increase (p<0.05) in body temperature,respiratory and heart rate. Furthermore, a significant (p<0.05) reduction of ruminal contractionsalso resulted. Hematological changes of diseased buffalo and the controls, reveals Leucocytosisdue to a significant increase of Nurtrophiles. All diseased animals are clinically examined andthe results reveals that Proteus mirabilis and Enterobacter cloacae are the common causes ofmastitis which confirmed by VITEK 2 System. The gram stain from the milk smears show aclear Gram-negative rods, Moreover, swarm forming and pale colony character was alsoindicated of the swab culture of the causative Proteus mirabilis. It has been concluded that acutebuffalo mastitis could be of adverse effect, Nevertheless, the knowledge of the causative agentsof mastitis are very useful for the fast treatment of the disease.